A Randomized Controlled Trial of Emotion Regulation Therapy for Psychologically Distressed Caregivers of Cancer Patients. Issue 1 (13th September 2019) - O'Toole, Mia S; Mennin, Douglas S; Applebaum, Allison; Weber, Britta; Rose, Hanne; Fresco, David M; Zachariae, Robert
Abstract: Background: Previous cognitive behavioral therapies for informal caregivers (ICs) have produced negligible effects. The purpose of this study was to evaluate, in a randomized controlled trial, the efficacy of Emotion Regulation Therapy adapted for caregivers (ERT-C) on psychological and inflammatory outcomes in psychologically distressed ICs and the cancer patients cared for. Methods: A total of 81 ICs with elevated psychological distress were randomly assigned to ERT-C or a waitlist condition and assessed pre-, mid-, and post-treatment. In 52 cases, the patient cared for by the IC was included. Patients did not receive ERT-C. Both the ERT-C and waitlist groups were followed 3 and 6 months post-treatment. Data were analyzed with multilevel models, and P values were two-sided. Results: Compared with ICs in the waitlist condition, ICs in the ERT-C condition experienced medium to large statistically significant reductions in psychological distress (Hedge's g  =   0.86, 95% confidence interval [CI] = 0.40 to 1.32, P < .001), worry ( g  =   0.96, 95% CI = 0.50 to 1.42, P < .001), and caregiver burden ( g  =   0.53, 95% CI = 0.10 to 1.99, P = .007) post-treatment. No statistically significant effects were found for rumination ( g  =   0.24, 95% CI = −0.20 to 0.68, P = .220). Results concerning caregiver burden were maintained through 6 months follow-up. Although the effects on psychological distress and worry diminished, their end-point effects remained medium to large. No statistically significant effects on systemic inflammation were detected (C-reactive protein: g = .17, 95% CI = −0.27 to 0.61, P = .570; interleukin-6: g = .35, 95% CI = −0.09 to 0.79, P = .205; tumor necrosis factor-alpha: g = .11, 95% CI = −0.33 to 0.55, P = .686). Patients whose ICs attended ERT-C experienced a large increase in quality of life post-treatment ( g  =   0.88, 95% CI = 0.18 to 1.58, P = .017). Conclusions: To our knowledge, this is the first randomized controlled trial evaluating the efficacy of ERT-C for ICs. Given the previous disappointing effects of other cognitive behavioral therapies for this population, the present findings are very encouraging. Identifying ICs with elevated psychological distress and providing them with relevant psychotherapy appears an important element of comprehensive cancer care.